Parity And Body Mass Index As Factors In Preeclampsia Incidence - SUSANTI, ELI; Ruspita, Mimi; Isharyanti, Septalia (Poltekkes Kemenkes Semarang, 2024)
The maternal mortality rate illustrates the number of maternal deaths per 100,000 live births, caused by interference during pregnancy, maternity and childbirth. Factors of preeclampsia are parity and obesity. The purpose of this study to determine the relationship between parity and BMI with the incidence of preeclampsia in QIM Batang Hospital Batang Regency in 2023. The research design used a case control and retrospective approach. Samples in this research was 220 pregnant women, Case Group 110 Respondents and Control Groups 110 Respondents. Data analysis using Chi-Square. The results showed that parity at risk of 55 case groups (50%) and parity at risk of control group 65 (59.1%). IMT is not normal case group 94 (85.5%) and IMT is not normal control group 74 (67.3%). The bivariate analysis shows that there is no relationship between parity and preeclampsia (0.176 0.05) but there is a significant relationship between the body's mass index and the preeclampsia in the Qim Hospital in Batang Regency (0.002 0.05). The results of this study can add insight in midwifery care to pregnant women. Pregnant women who have abnormal BMI are advised to maintain diet so that there is no weight gain.